Professional practices of education/training of nurses in an intensive care unit - Ana Paula Morais de Carvalho Macedo; Katia Grillo Padilha; Vilanice Alves de Araújo Püschel (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To understand the education/training of nurses working in an intensive care unit. Method: Case study with qualitative approach, with an intentional sample. Data collection and analysis used different research techniques, mainly document analysis, interview and field observation. Results: The data highlights feelings of well-being, satisfaction and motivation as important for education and training in a work context. Some organizational practices seem to promote interpersonal relationships and, consequently, increase the willingness of these professionals to adopt a reward perspective regarding continuing education and training, establishing a close relationship between the formal, the non-formal and the informal. Final Consideration: The attractiveness of this organization is related to the valorization and recognition that it can offer to the professionals. There is a reciprocity between a hospital that endorses up-to-date care and professionals who seek scientific evidence.